The proxy advisory industry: Influencing and being influenced - Shu, Chong (Journal of Financial Economics, 2024)
This paper develops two new methods to infer a mutual fund's proxy advisors from SEC filings. It then applies these methods to characterize features of the proxy advice industry from 2007 to 2021: (i) As of 2021, ISS and Glass Lewis collectively control approximately 90 percent of the market. During this period, the market share of ISS remains stable, while that of Glass Lewis has increased. (ii) When a proxy advisor issues a recommendation opposing management, its customers are approximately 20 percentage points more likely to also oppose management compared to other investors. (iii) Funds that subscribe to both proxy advisors tend to vote more similarly to the recommendations of the advisor whose voting platform they use. (iv) Proxy advisors often change their advisory stance when investors disagree with their previous advice. I offer suggestive evidence that this adaptation reflects both learning from informed investors and a desire by proxy advisors to align with the preferences of their customers.